VO2MAX LEVELS AS A POINTER OF PHYSIOLOGICAL TRAINING STATUS AMONG SOCCER PLAYERS - Zerf Mohammed, Bengoua Ali, Mokkedes Moulay Idriss Boras Fatima Zohar, Benali Gourar, Bengoua Ali, Mokkedes Moulay Idriss (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2018)
Summary: The purpose of the current study was to evaluate the Aerobic endurance training as indicators of physiological training status among male soccer players. A total of 138 well-trained first division soccer players under 18 years were tested. Testing was based on the Cooper test as a one of simple tests to estimate VO2max. BMI and BFP as valued anthropometric measurements to control body change relative to maximal oxygen consumption during dynamic exercise with large muscle groups benefit training time soccer training experience. Performance in this experience was based on the subjection that 60 ml/kg/min of VO2max is the minimum fitness requirement for male soccer players to play at the elite level. Admit in this study as a protocol to categorise our sample into two groups (up and under the range VO2max ± 60 ml/kg/min) and it was based on statistics applied and the design used. Our results highlighted the importance of aerobic performance up to 60 ml/kg/min as the minimum fitness requirement to enhance the players' aerobic capacity allied to maximal heart rate relative to BFP levels as a better parameter in comparison with BMI for the prediction of low VO2max concomitant to the physiological training status as requests soccer performance demand.
Keywords: BFP, BMI, VO2max, physiological, soccer player